Exploring how brain health strategy training informs the future of work - Zientz, Jennifer; Spence, Jeffrey S.; Chung, Susan Sung Eun; Nanda, Upali; Chapman, Sandra Bond (Frontiers in Psychology, 2023)
In this research conducted during the changing remote work practices emerging post-pandemic, we tested the hypothesis that a capacity-building training would be associated with significant gains on measures of brain health and components of burnout and influenced by days in office for individuals to inform workplace practices. We measured brain health with an evidenced-based measure (BrainHealth™ Index) with its components that include the key elements from the World Health Organization definition. Brain health is defined as the promotion of optimal brain development, cognitive health, and well-being across the life course, which we expanded to also include connectedness to people and purpose. The workplace typically affords one of the longest periods for continued brain health growth. This work was motivated by prior work showing individuals, outside of an aggregate setting, benefitted from training as measured by significant performance gains on a holistic BrainHealth Index and its factors (i.e., clarity, connectedness, emotional balance). Presently, we investigated whether 193 individuals across a firm’s sites would benefit from micro-delivery of online tactical strategies, combined with two individualized coaching sessions, and practical exercises related to work and personal life, over a six-month period. Results at posttest indicated that individuals showed significant gains on a composite BrainHealth Index and across all three composite factors contributing to brain health. The current results also found an association between gains on both the connectedness and emotional balance brain health factors and reduced burnout components of occupational exhaustion and depersonalization towards one’s workplace. We found that fewer days in office was associated with greater gains in the clarity factor, but not for connectedness and emotional balance. The latter two factors are important for team work and strong culture. These results support the value of a proactive, capacity-building training across employees to complement a small segment who are also in need of mental illness assistance programs. The future of work may be informed by corporate investment in focused efforts to boost brain capital through a human-centered, capacity-building approach, as evidence emerges, with needed efforts to uncover the economic and individual benefits of better brain skills or Brainomics©.